Trust, Tax Complexity, and Digital Transformation: Determinants of Tax Compliance - Rawun, Yuli; Murwaningsari, Etty; Aryati, Titik (Moestopo International Review on Social, Humanities, and Sciences, 2026)
Tax compliance constitutes a persistent governance challenge in Indonesia, where institutional trust deficits and regulatory complexity persistently undermine voluntary fiscal adherence. This study pursues four objectives: (1) to examine the direct effect of institutional trust on voluntary fiscal adherence; (2) to assess the impact of tax complexity on compliance behavior; (3) to determine whether Digital Transformation moderates the trust-to-compliance relationship; and (4) to evaluate whether Digital Transformation attenuates tax complexity’s adverse effect on adherence. Grounded in the Slippery Slope Framework, Compliance Theory, and the Technology-Organization-Environment (TOE) Framework, a quantitative survey design was employed. Primary data were collected from 396 active tax consultants registered with the Indonesian Tax Consultants Association (IKPI), selected via criterion-based purposive sampling from 450 distributed questionnaires. Partial Least Squares Structural Equation Modeling (PLS-SEM) was applied using SmartPLS 4.0 with 5,000 bootstrap subsamples. Results reveal that institutional trust exerts no significant direct effect on compliance, whereas tax complexity significantly impairs adherence. Digital Transformation operates as a pure moderator enhancing the trust-compliance pathway and as a quasi-moderator mitigating complexity’s adverse influence, collectively explaining 50.6% of variance. These findings confirm Digital Transformation as a pivotal institutional lever for evidence-based fiscal governance reform in emerging economies.